A Study on The Impacts of Colonial Plantations in Wayanad - Babu Kannothumkandy (Kurdish Studies, 2022)
Plantation is a large-scale farm that specialises in cash crops. The crops grown include coffee, tea, rubber, cinnamon, Cardamom, etc. It is usually large farms or states, especially in a tropical or semi-tropical country, on which cash crops are cultivated. European powers like the Portuguese, Dutch, British, and French explored new places and colonised them for an extended period. This marked the emergence of a new phenomenon, ‘Colonialism’ worldwide. Among these powers, the British had colonised most of the world. During colonisation, they arrived in India and ruled us for centuries. To exploit our wealth, they introduced various reforms. They converted our land into a colony, a feeding centre of their revenue. Waging wars was one of the methods by which the British expanded their colonial boundaries. In the second Anglo-Mysore war, they defeated the Mysore ruler, and, as per the Srirangapattnam treaty of 1792, they got Malabar. When the British became the custodian of Malabar in 1799, they introduced many reforms. One among them was Agrarian reforms. It was based on Agrarian reforms that the British started plantations like tea, coffee, rubber, etc in the Wayanad region. The socio-economic improvement of Wayanad was the direct result of plantation in the area. The present study, ‘Colonial Plantations and its impact in Wayanad’, attempts to analyse the Europeans' establishment of the plantation industry in Wayanad regions and its effect on the socio-economic life in that area.